Diseño de una planta agroindustrial para la producción de alimentos de chocho (Lupinus Mutabilis Sweet) en Cotopaxi - Camposano Jaramillo, Juan Francisco (2017)
This titling work was based on the design of an agroindustrial plant to produce processed chocho’s food (Lupinus mutabilis sweet) in the Province of Cotopaxi, whose purpose was to boost the economy and development of small producers in the area. In order to know if it is feasible the development of food products based on chocho a closed survey was carried out to 278 people in zone 4 of the Metropolitan District of Quito that were chosen randomly within the population that lives in this zone. With the information obtained from the surveys, it was possible to observe the demand on the proposed products that were: milk, yogurt, bread and empanada, and in this way it was possible to budget machinery for the production of these products. Having the machinery proceeded to design the processes that each product needs to be elaborated, this was achieved by carrying out process flows and mass balances. With the flows and balances made, we proceeded to design the agro-industrial plant using the AutoCAD design program, taking into account spaces necessary for an optimal work in the plant, machinery, hallways, personnel, among others were distributed in the most appropriate way according to our flows. Finally, a cost benefit analysis was performed in which the viability of the project was determined.